Hourly streamflow forecasting with ARMA models for maximizing hydropower revenues - Rodero, Augusto O. (2010)
Hydrologic streamflow forecasting has always been a concern for water resources engineers for optimal operations of water systems. The autoregressive - moving average (ARMA) models is a group of stochastic models popularly used by modelers over the past decades as a tool for streamflow forecasting.
The necessity for a good hourly streamflow forecasting model has never been more valuable to operators of hydropower plants. With the enactment of the Electric Power Industry Reform Act, 2001 (EPIRA), the operators are required to submit a day-ahead forecast generation to the National Grid Corporation of the Philippines (NGCP) for its next 24-hour generation. Changes for imbalance (over/under) generation are now in effect.
This paper has illustrated that with the development of an hourly ARMA forecasting model for the operation of the 16.5MW Sibulan-A hydropower plant (HPP); charges for imbalance generation can be minimized and eventually led to maximized hydropower revenue.
A step-by-step procedure of model construction was presented on the hourly data of the mentioned powerplant. It was highlighted that the final models were chosen was based on how sound the models are in 24-hours ahead forecasting applications.
It was demonstrated that operating Sibulan-A with ARMA forecasting yielded more revenues at an average of Php 14,000.000. Compared to operating the HPP by simply assuming that past 7-day hourly mean is the forecast for the next 24-hours.
"October 2010"
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Hydrological forecasting; Hydrologic models; ARMA (Autoregressive Moving Average).